Design of Wideband Third-Order Bandpass Filters Using Broadside-Coupled Resonators in 0.13- μ m (Bi)-CMOS Technology - Zhu, He; Zhu, Xi; Yang, Yang; Xue, Quan (IEEE transactions on microwave theory and techniques, 2018)
In this paper, two third-order bandpass filters (BPFs) designed for millimeter-wave applications are presented. Unlike previously published ones, the proposed designs use a "cell-based" approach, which utilizes identical broadside-coupled resonators (BCRs) with series and shunt capacitors. The capacitors are mainly used as J-inverters to achieve the desired frequency responses. To fully understand the operational mechanism of the presented approach, both the BCR and BPFs are analyzed using the simplified LC-equivalent circuit models. To prove the concept, both BPFs are implemented in a standard 0.13-μm silicon-germanium bipolar complementary metal-oxide-semiconductor technology. According to the on-wafer measurement results, the BPFs exhibit the excellent performance including flat in-band responses with relatively large harmonic suppression. The first design has a 1-dB bandwidth from 23.9 to 39.7 GHz with an insertion loss of 3.9 dB at the center frequency of 31 GHz. The stopband attenuation is better than 45 dB at 58 GHz. The 1-dB bandwidth of the second design covers from 26.7 to 44.3 GHz with an insertion loss of 3.1 dB at the center frequency of 35 GHz, and stopband attenuation up to 35 dB is achieved at 59 GHz. Both designs occupy an identical area of 0.073 mm 2 (0.248 × 0.294 mm 2 ), excluding the G-S-G testing pads.